IDENTIFIKASI JENIS MANGROVE DI KAWASAN PANGKAL BABU, DESA TUNGKAL 1, KECAMATAN TUNGKAL ILIR, TANJUNG JABUNG BARAT JAMBI - riris roiska; Dedi Damhuri; Putinur (JURNAL BIOSENSE, 2026)
Mangroves are coastal forest ecosystems commonly distributed in tropical and subtropical regions and play a vital role in maintaining coastal environmental stability. The mangrove ecosystem in Pangkal Babu, Tungkal 1 Village, Tungkal Ilir District, West Tanjung Jabung Regency, Jambi, functions as an ecological buffer for the coastal zone; however, scientific information on its species composition and diversity remains limited. This study aimed to identify and document the mangrove species present in the area. Field surveys and direct observations were conducted to characterize mangrove vegetation by recording and photographing each species and examining diagnostic features, including root structure, stem morphology, leaf shape, and fruit characteristics. The results showed that the Pangkal Babu mangrove ecosystem is composed of several true mangrove species, each exhibiting distinctive morphological traits: Acanthus ilicifolius with thick spiny leaves; Nypa fruticans with large pinnate leaves and clustered fruits; Sonneratia alba with erect pneumatophores and subglobose fruits; Avicennia alba with salt-excreting leaves and pencil-shaped pneumatophores; Bruguiera cylindrica with knee roots and cylindrical propagules; Rhizophora mucronata with mucronate leaves and large stilt roots; Rhizophora apiculata with black-spotted leaves and shorter propagules; and Xylocarpus granatum with compound leaves and large spherical fruits resembling cannonballs. These findings provide essential baseline data for future conservation efforts, habitat monitoring, and sustainable coastal management initiatives in Tungkal Ilir and the surrounding regions.